Self-performed supragingival biofilm control: qualitative analysis, scientific basis and oral-health implications - Sheila Cavalca Cortelli; José Roberto Cortelli; Davi Romeiro Aquino; Fernando Oliveira Costa (Sociedade Brasileira de Pesquisa Odontológica, 2010)
Patients frequently fail to achieve an optimal mechanical plaque control. However, many patients are not confident about using mouthrinses, and many professionals refuse to prescribe them for regular daily use. Aiming at achieving a better understanding of the use and prescription of mouthrinses in periodontics, 24 dentists with different dental educational levels were purposively chosen and interviewed in a qualitative research. Partial data was presented at the 15th Congress of the Brazilian Association for Oral Health Promotion (ABOPREV), and full data was presented at the 88th General Session and Exhibition of the International Association for Dental Research (IADR). The professionals' answers were confirmed or rejected through scientific data analysis. Additionally, scientifically supported answers were provided for the interviewees' most frequent unanswered questions. Around half of the participants (46%) reported that they recommended the use of mouthrinses, although a high percentage (64%) of the dentists answered that they knew very little about the efficacy of mouthrinses and also about the oral benefits (54%) provided by them. All interviewees reported that they were aware of the fact that their patients, and themselves, failed to floss and, less frequently, to brush their teeth, and all of them believed that oral health impacts overall systemic health. Seventy five percent answered that using mouthrinses was safe. Most participants (55%) did not declare themselves as mouthrinse users. We concluded that dentists with different levels of dental education have only partial knowledge related to mouthrinse use in periodontics. The use of effective mouthrinses on a daily basis is justified and can help patients achieve or maintain a healthier mouth. A healthier mouth will positively impact patients' quality of life and could also benefit their overall systemic health.